The Influence of Stress on Learning Leadership Project Assignment Test PT PLN (Persero) - Zulfana, Dewi; Wibowo, Eddy Kusponco; Widjayanti, Arifiani (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study aims to determine the role of stress on leadership learning participants in the Project Assignment (PA) test of PT Perusahaan Listrik Negara (PLN) (Persero). This study uses a quantitative approach using mixed survey data collection techniques distributed to 150 respondents in this case leadership course participants. The results showed a significance value of 0.505> 0.050, it can be concluded that there is no significant effect of the PT PLN (Persero) PA test on participants. Based on the results of respondents' research, the symptoms of stress that appear in the PA test are the behaviour of lack of confidence and not being able to control themselves when taking the PA test. Other factors that influence the implementation of the PA test at PT PLN (Persero) are time constraints (24%), examiners/guides/mentors (23%), methods/materials (16%), communication skills (15%), workload (9%), and others 13%. Stress in leadership trainees needs to be managed properly by providing positive stress management materials to manage stress and increase motivation.